2018
DOI: 10.1038/s41598-018-28568-7
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Removal in Relation to Structural Development of Humic Acid-Iron Coprecipitates

Abstract: Precipitation of Fe-hydroxide (FH) critically influences the sequestration of PO4 and organic matter (OM). While coatings of pre-sorbed OM block FH surfaces and decrease the PO4 adsorption capacity, little is known about how OM/Fe coprecipitation influences the PO4 adsorption. We aimed to determine the PO4 adsorption behaviors on humic acid (HA)-Fe coprecipitates in relation to surface and structural characteristics as affected by HA types and C/(C + Fe) ratios using the Fe and P X-ray absorption spectroscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…In contrast, a strong positive correlation between Fe and P in shells of mollusks may indicate either P co-precipitation with Fe hydroxide or formation of Fe phosphate at the shell surface or impregnated between growing layers. Strong removal of P with Fe hydroxide from aqueous solutions is fairly well known [24][25][26]. The importance of this process for concomitant Fe and P accumulation in mollusks shells is consistent with the fact that the K d Shell/Water for Fe and P did not exhibit statistically significant regression relationships with the distance from the mouth of the Severnaya Dvina River (p > 0.05), despite sizable variations of these element concentrations in the river water.…”
Section: Element Inter-correlations and Element Ratios As Indicators Of Possible Mechanisms And Environmental Conditionssupporting
confidence: 65%
“…In contrast, a strong positive correlation between Fe and P in shells of mollusks may indicate either P co-precipitation with Fe hydroxide or formation of Fe phosphate at the shell surface or impregnated between growing layers. Strong removal of P with Fe hydroxide from aqueous solutions is fairly well known [24][25][26]. The importance of this process for concomitant Fe and P accumulation in mollusks shells is consistent with the fact that the K d Shell/Water for Fe and P did not exhibit statistically significant regression relationships with the distance from the mouth of the Severnaya Dvina River (p > 0.05), despite sizable variations of these element concentrations in the river water.…”
Section: Element Inter-correlations and Element Ratios As Indicators Of Possible Mechanisms And Environmental Conditionssupporting
confidence: 65%
“…In addition to more surface functional groups, group B had the characteristics of strong silicide activity. Moreover, the organic matter removal (organic degradation in sediment) would reduce the polar functional groups and reduce the activity of silicide, and lead to heavy metal desorption and re-entry into the water body [44]. Therefore, it was observed that the adsorption capacity of the organic matter-clay mineral complex in group B was higher than that of group A inorganic minerals.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…Both of them have remarkable anti-biodegradation properties, which allows for their long-term stability in soil (Chen et several studies proposed that HS does not signi cantly affect the adsorption behavior of iron oxide (Borggaard et al 2006;Weng et al 2009). Khouri et al (1995) suggested that the inhibition of phosphate adsorption by OM was temporary, while Chen et al (2018) found that coprecipitates of ferrihydrite and OM yield P sorption properties nearly equivalent to that of pure ferrihydrite.…”
Section: Introductionmentioning
confidence: 99%